Pharmacist Impact on Immunization Rates in Asplenic Patients - Deidra Van Gilder; Shanna K O'Connor (University of Minnesota Libraries Publishing, 2022)
Background: Asplenic patients can present unique challenges when updating immunizations. Pharmacists have proven to have a positive impact on immunization rates in asplenic patients. Objectives: To determine the impact of pharmacist intervention on the up-to-date immunization status in asplenic patients in a single rural family medicine clinic and identify quality improvement opportunities for the immunization service. Service Description: The pharmacist obtained an initial list of asplenic patients to create a longitudinal tracking spreadsheet for immunizations that identified missing vaccines for each patient; provider education on vaccine needs in this population and the service was also provided. The ongoing service consists of regular updates to the spreadsheet as patients receive vaccines and a quarterly check of the entire spreadsheet to determine needed vaccines; if needed vaccines are identified, the pharmacist facilitates a patient appointment to obtain the vaccine. Methods: A retrospective chart review was completed in Spring 2022 for all patients included in the baseline report. Patients were categorized based on vaccine status and outstanding vaccines were noted. An evaluation was completed to determine if any identifiable trends across providers were evident based on patient immunization status. Results: A total of 33 asplenic patients were identified at baseline; three (9%) were up-to-date at baseline. Of the 30 patients who were maintained in the clinic, 16 (53.5%) were up-to-date at the point of review. Pharmacist intervention increased the total vaccine completion rate by 44.5% from baseline to follow-up. The biggest improvement for a specific immunization status was made on the meningitis b vaccine; Haemophilus influenzae b showed the highest completion rate at follow-up. No trends were noted across providers that indicated why some providers had patients with higher immunization rates than others. Conclusion: Pharmacist intervention contributed to an increase in immunization rates in a single immunocompromised patient population that requires a specialized immunization schedule.